Anisotropic mechanical properties of Si anodes in a lithiation process of lithium-ion batteries - Wang, D.; Wang, Y.; Zou, Y.; Lu, Chunsheng; Ma, Zengsheng (Springer Vienna, 2018)
© 2018 Springer-Verlag GmbH Austria, part of Springer Nature High-capacity active electrodes, such as Si anodes in Li-ion batteries, undergo a significant volume deformation of up to (Formula presented.) 400% during lithiation. Such a huge volume change could cause mechanical fracture and pulverization of electrode materials and result in harmful effects on their electrochemical performance. To have better understanding on this problem, the two-phase lithiation process of hollow core–shell and film structural electrodes is simulated by using a diffusion lithiation model. It is shown that the anisotropic hoop stress is larger than the isotropic one, which may easily induce damage of hollow core–shell negative electrodes. In addition, the anisotropic nature of mechanical properties can also remarkably magnify the edge stress intensity factor of hollow core–shell and film electrodes. These results on the morphological evolution and stress generation shed light on the design of novel and failure-resistant electrodes.